LOW FAULT FRICTION IN IRAN IMPLIES LOCALIZED DEFORMATION FOR THE ARABIA-EURASIA COLLISION ZONE - Vernant P.; Chéry J. (My University, 2006)
The GPS velocity field of the present-day deformation in Iran is modeled using a 3-dimensional (3D) finite element approach. The deformation can be accommodated either by a continuum medium or by faults which are modeled using discontinuities with Coulomb-failure criteria. Depending on the fault friction, the deformation will be accommodated by the continuum medium or by the faults. Therefore, no a priori hypothesis on continuum or microplate behavior is assumed. In addition, geological fault slip rates are used to better determine the optimum model. The best model fitting both GPS and geological data shows quasi-rigid blocks within the deformation zone and low effective fault friction for the main Iranian strike slip faults. The mechanical behavior of the Iranian lithosphere seems to be partly controlled by the large strike slip faults. However, some deformation is still taken up by the continuum medium, suggesting a compromise between the microplate and continuum descriptions. Results also suggest localized shear zones in the mantle underneath the crustal faults bordering the quasi-rigid blocks. Lastly, the Arabia push relative to Eurasia explains most of the kinematics in Iran, but the complex velocity field of the surrounding South Caspian basin cannot be fitted by this model. Therefore, slab pull due to a remnant oceanic crust may occur in the Caucasus-Caspian region. © 2006 Elsevier B.V. All rights reserved.
Keywords: 3D MODELING; FAULT SLIP RATE; GPS; IRAN